Physician Prescribing of Opioids to Patients at Increased Risk of Overdose From Benzodiazepine Use in the United States - Ladapo, Joseph A. (JAMA Psychiatry, 2018)
IMPORTANCE: Recent increases in US opioid-related deaths underscore the need to understand drivers of fatal overdose. The initial prescription of opioids represents a critical juncture because it increases the risk of future opioid use disorder and is preventable. OBJECTIVE: To examine new opioid prescribing patterns in US patients at increased risk of overdose from benzodiazepine use. DESIGN, SETTING, AND PARTICIPANTS: This study used publicly available data from the National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey from January 1, 2005, through December 31, 2015, to identify adults 20 years or older receiving new opioid prescriptions and concurrently using a benzodiazepine. MAIN OUTCOMES AND MEASURES: Population-based rates of new opioid prescriptions stratified by use of benzodiazepines. RESULTS: This study analyzed 13 146 visits, representing 214 million visits nationally, with a new opioid prescription. Rates of new opioid prescriptions among adults using a benzodiazepine increased from 189 to 351 per 1000 persons between 2005 and 2010 (rate difference, 162; 95% CI, 29-295; P = .02) and decreased to 172 per 1000 persons by 2015 (rate difference, −179; 95% CI, −310 to −48; P = .008). New opioid prescriptions in the general population not using benzodiazepines increased nonsignificantly from 78 to 93 per 1000 US persons between 2005 and 2010 (rate difference, 15; 95% CI, −3 to 33; P = .10) and decreased nonsignificantly to 79 per 1000 persons by 2015 (rate difference, −14; 95% CI, −38 to 11; P = .28). The likelihood of receiving a new opioid prescription during an ambulatory visit remained higher for patients concurrently using benzodiazepines compared with the general population after adjusting for demographic characteristics, comorbidities, and diagnoses associated with pain (adjusted relative risk, 1.83; 95% CI, 1.56-2.15; P < .001). Naloxone was coprescribed in less than 1% of visits when a patient concurrently used a benzodiazepine. CONCLUSIONS AND RELEVANCE: In 2010, new opioid prescriptions for US adults stopped increasing and began to decrease among higher-risk patients who used benzodiazepines. These patterns suggest that the recent increase in opioid-related deaths may be associated with factors other than physicians writing new opioid prescriptions. Nevertheless, prescribing among higher-risk patients still occurred at rates higher than rates in the general population, representing an important opportunity to improve quality of care for patients experiencing pain.